Modeling stepped U‐slot DGS microstrip line. Issue 3 (March 2016) - Woo, Duk‐Jae; Lee, Taek‐Kyung; Nam, Sangwook
ABSTRACT: This paper presents an equivalent circuit model for a stepped U‐slot defected ground structure (DGS). For a stepped U‐slot DGS, the defected structure is simply modeled using a short‐circuited stepped impedance coplanar waveguide (CPW) combined with a gap capacitor. The proposed circuit model is advantageous in its ability to accurately control the ratio ( η  =  fs 1 /fr ) of the fundamental resonance frequency ( fr ) to first spurious resonance frequency ( fs 1 ) by changing the impedance and the electrical length of the CPW in each step. By using this property, two types of resonators with normalized first spurious resonance frequencies ( η  =  fs 1 /fr ) of 4 and 2 were designed and fabricated. Good agreement between the EM simulations and the experimental results were achieved. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:583–587, 2016